ANALISIS PENEGARUH PERALIHAN PENGELOLAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN LOMBOK TENGAH - Ika Srikomalasari; Muhammad Sayuti; Baiq Rizka Milania Ulpah (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This research is Entitled "Analysis Of The Influence Of The Transfer Of Management Of Land And Building Rights On Regional Original Income Of The Central Lombok District". In this research, the researcher wants to see how the transition in management of land and building rights affects regional indigenous income generation in Central Lombok Regency. This type of research is quantitative research with an associative approach. The analytical tool used in this research is simple linear regression analysis. The results of this research are that from the results of the regression analysis regarding the influence of BPHTB on Central Lombok Regency's PAD, BPHTB does not have a significant effect on Central Lombok Regency's PAD revenue. This is because the estimation results show that the significance value of BPHTB is greater than the alpha level used, namely 5% ((0.286 > 0.050) or the calculated T value is smaller than the T table value (1, 295 > 2.776). From the results of the R-value Square obtained a result or value of 0.359 with a significance value (α) or alpha of 0.05 (5%). The R-square value in this study has meaning, namely the influence of the BPHTB variable on PAD in Central Lombok Regency, namely 35.9% while the remaining amounting to 64.1% is influenced by other variables that are not included in this research, such as taxes, levies, other legitimate PAD sources and several other items that are included in the PAD forming category. Meanwhile, from the results of the analysis of the effectiveness of Central Lombok Regency BPHTB revenues, that BPHTB revenue is included in the effective category, this can be seen from the percentage of revenue realization exceeding 100%.